2017
DOI: 10.1016/j.coviro.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Novel viral and host targets to cure hepatitis B

Abstract: Hepatitis B virus (HBV) infection is a global health threat with 240 million chronic carriers at high risk to develop hepatocellular carcinoma. Current antiviral treatment can efficiently control viral replication and reduce liver inflammation, but is still quite far from achieving a cure. Significant progress has been made in understanding the virus life cycle and virus-host interaction in the past few years. With identification of the HBV receptor, cell-culture infection systems have become available that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…A number of exciting new approaches are under development targeting different stages of the HBV lifecycle (3)(4)(5). However, it is unlikely that future antiviral drugs will be able to clear every trace of cccDNA from the large burden of infected hepatocytes.…”
Section: Rational For An Immunotherapeutic Approachmentioning
confidence: 99%
“…A number of exciting new approaches are under development targeting different stages of the HBV lifecycle (3)(4)(5). However, it is unlikely that future antiviral drugs will be able to clear every trace of cccDNA from the large burden of infected hepatocytes.…”
Section: Rational For An Immunotherapeutic Approachmentioning
confidence: 99%
“…HBV uses cellular transcriptional machinery to support viral gene expression . In fact, efficient transcription of HBV genes requires both viral proteins and host transcription factors.…”
mentioning
confidence: 99%
“…(7,8) HBV uses cellular transcriptional machinery to support viral gene expression. (9) In fact, efficient transcription of HBV genes requires both viral proteins and host transcription factors. The expression of viral HBx protein has been shown to be essential for efficient HBV transcription by inducing degradation of the host restriction factor "structural maintenance of chromosomes" (Smc) complex Smc5/6.…”
mentioning
confidence: 99%
“…Recent studies growingly revealed the significance of host cellular factors in the viral life cycle [46] and also carcinopathogenesis [47,48]. Exemplarily, cyclophilin (CyP) has been demonstrated to be a critical host cellular factor [49].…”
Section: Discussionmentioning
confidence: 99%